New Species Assemblages Disrupt Obligatory Mutualisms Between Figs and Their Pollinators - Bernard, Jared; Brock, Kelsey C.; Tonnell, Veronica; Walsh, Seana K.; Wenger, Jonathan P.; Wolkis, Dustin; Weiblen, George D. (Frontiers in Ecology and Evolution, 2020)
The reliance of each fig species on its specific pollinator wasp, and vice versa, is the archetype of both obligatory mutualism and coevolution. Pollinator sharing between host fig species is only known to occur among closely related sympatric species. On the Hawaiian island of Kauai, we gathered syconia from 23 non-native fig species, three of which contained the wasp Pleistodontes imperialis. Of the three fig species, one is the wasp’s natural host, Ficus rubiginosa, and another is its sister species, F. watkinsiana, which overlaps in native ranges, although researchers have not previously documented pollinator sharing. The third fig species, F. rubra, is distant to the others both in terms of phylogenetic relationship and native range. We found viable seeds for all three fig species, whereas species without wasps did not produce seeds. To investigate similarity between these pollinator-sharing fig species, we collected morphometric data for syconia of our study fig species. We found that fig species with and without P. imperialis significantly differ based on the orientation of their inner ostiolar bracts. These findings suggest that pollinator sharing among these three fig species may normally be impeded by pollinator competition in the case of F. watkinsiana, and by geographic distance in the case of F. rubra. This work therefore demonstrates that coevolution depends on interactions within native species assemblages, and that mutualisms can be disrupted in new non-native communities.